Solving the House Deficit Problem in Kinshasa by Building Affordable Houses Through the PPP Project Delivery - Min, Song Jian; Mayuka, Ruth Nzinga; Joseph, Annan Joseph; Qiaomin, Zhang Qiaomin; Mangweji, Rachel Mangweji (International Journal of Computing and Engineering, 2023)
Purpose: The introduction of the Public-Private-Partnership (PPP) in the delivery of low-cost houses in Congo is a recent phenomenon. The article will investigate the factors behind this new strategy of building affordable houses and try to establish how PPP can contribute to better housing for the residents of the most populated city of Congo (Kinshasa). The study focuses on the factors contributing to the increasing demand for the Public-Private-Partnership in the construction of affordable housing projects introduced by the Government. Methodology: For us to obtain the perspectives of key participants in the public sector dealing with the delivery of affordable housing projects in Kinshasa, an in-depth semi-structured interview and survey were conducted. This method combines qualitative and quantitative data collection techniques Findings: The result of the analysis shows that there are four main reasons for this increment: The lack of public resources, the high demand for low-cost housing, the Lack of qualified construction workers, and the lack of the private sector's interest to invest in social housing. Unique Contributions to Theory, Policy and Practice: The challenges of delivering low-cost house projects are numerous. The challenges are divided into different categories: political and economic, Governance, international forces, administration, financial resources, material resources, management practices, technical, and local external pressures, and natural forces are some of the issues that need to be addressed. While politics and governance, administration, financial and material resources, local external pressures, and environmental forces are all important, the performing organization faces external problems, as well as management and technical challenges.